2000
DOI: 10.1017/s0021932000000638
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Health-Related Behaviours and the Risk of Divorce in the Usa

Abstract: This study investigates the link between health-related variables and risks of divorce. The findings indicate that physical characteristics associated with poor health -namely, obesity and short stature -are not significantly related to risks of marital dissolution for either men or women. On the other hand, risk-taking behaviours -such as smoking and drug useare strongly related to higher risks of divorce for both sexes. Overall, the results emphasize the need to accommodate health-related variables in the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Contrasting findings derive from the US National Longitudinal Survey of Youth, a study featuring a comparable research design. Although short men exhibited lower rates of first marriage than those of average height, this effect disappeared once family-of-origin variables (parental education, poverty status, and region of the country) were taken into account; no consistent relationship was found between women’s height and marriage rates [49, 50]. …”
Section: Qol Assumptions Regarding Short Stature and Supporting Evidementioning
confidence: 99%
“…Contrasting findings derive from the US National Longitudinal Survey of Youth, a study featuring a comparable research design. Although short men exhibited lower rates of first marriage than those of average height, this effect disappeared once family-of-origin variables (parental education, poverty status, and region of the country) were taken into account; no consistent relationship was found between women’s height and marriage rates [49, 50]. …”
Section: Qol Assumptions Regarding Short Stature and Supporting Evidementioning
confidence: 99%
“…Several cross-sectional analyses of marital status in general find that divorced and widowed people weigh less and are less likely to be obese than those who are married (Hayes and Ross, 1987;Sobal et al, 1992), although Fu and Goldman (2000) found no relationship between weigh and being divorced and Evers (1987) reported that widowed women were more likely to be obese than other women. Analyses of elderly samples find widows weigh less (Posner et al, 1993) or are no different in weight than those who are married (Himes, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, results from the ECA study showed that lifetime AUD did not predict higher odds of separation/ divorce over 1 year (Bruce, 1998). Fu and Goldman (2000) did not fi nd the hypothesized association between alcohol involvement and marital dissolution in a longitudinal study. Indeed, their results showed that moderate alcohol use among men was associated with lower risk of divorce (cf.…”
mentioning
confidence: 75%
“…For example, Collins et al (2007) showed that frequency of intoxication (but not frequency of marijuana use, frequency of cigarette smoking, or any hard drug use) was longitudinally associated with divorce. Contrary to the hypothesis that AUD might have a unique association with marital dissolution, epidemiological studies have found associations between marital dissolution and other substance use and psychiatric disorders, including illicit drug use (Compton et al, 2007;Fu and Goldman, 2000;Kandel et al, 1986); tobacco use (Chassin et al, 1992;Doherty and Doherty, 1998;Fu and Goldman, 2000); and mood and anxiety disorders (Chatav and Whisman, 2007;Kessler et al, 1998;Merikangas, 1984).…”
Section: Is the Association Between Alcohol Use Disorder And Marital mentioning
confidence: 97%
See 1 more Smart Citation